2016
DOI: 10.1007/s13365-016-0459-y
|View full text |Cite
|
Sign up to set email alerts
|

Progressive multifocal leukoencephalopathy in a patient without apparent immunosuppression

Abstract: Progressive multifocal leukoencephalopathy (PML) is a viral demyelinating disease due to the reactivation of the JC virus (JCV), which usually occurs in the context of immunosuppression in HIV infection, malignancy, or in patients on disease modifying therapy for autoimmune diseases, such as multiple sclerosis (MS) and Crohn's disease. Notably, there is growing recognition that PML can occur in patients with transient immune dysfunction. Here, we present a case of a 55-year-old man without history of immunosup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…15,16 In addition, several case reports on immunocompetent patients developing PML have also been published. 17,18 A relatively thin, uniformly linear SWI-hypointense rim was observed in 13 of 18 patients with PML in our study. The rim exclusively affected the U-fibers, following the cortical architecture, and did not correlate with other MR imaging findings.…”
Section: Discussionsupporting
confidence: 55%
“…15,16 In addition, several case reports on immunocompetent patients developing PML have also been published. 17,18 A relatively thin, uniformly linear SWI-hypointense rim was observed in 13 of 18 patients with PML in our study. The rim exclusively affected the U-fibers, following the cortical architecture, and did not correlate with other MR imaging findings.…”
Section: Discussionsupporting
confidence: 55%
“…29 CD4 lymphocytopenia, occurring as in idiopathic CD4 lymphocytopenia, has been linked to PML. 30 FAEs are known to reduce CD4 + and CD8 + lymphocytes, 31,32 and in all eight cases of PML reported in patients on FAE treatment, exposure to moderate-to-severe lymphocytopenia was present. FAE-induced moderate lymphocytopenia with more pronounced selective reductions in lymphocyte-subsets could predispose to an increased risk for PML.…”
Section: Discussionmentioning
confidence: 93%
“…Experimental studies have shown that FAEs induce lymphocytopenia, including reduction of CD4 + , CD8 + and B lymphocytes . CD4 lymphocytopenia, occurring as in idiopathic CD4 lymphocytopenia, has been linked to PML . FAEs are known to reduce CD4 + and CD8 + lymphocytes, and in all eight cases of PML reported in patients on FAE treatment, exposure to moderate‐to‐severe lymphocytopenia was present.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, PML occurs almost exclusively in immunosuppressed individuals. However, there are isolated case reports of PML in patients without apparent immunosuppression [6]. In a retrospective population-based analysis of a health insurance database, the incidence rates of PML in patients with autoimmune vasculitis was 10.8 per 100 000 person years [7].…”
Section: Discussionmentioning
confidence: 99%